MO425RENAL SURGERY APPROACHES AND POST-OPERATIVE AKI DEVELOPMENT IN NORMAL RENAL FUNCTION PATIENTS; AN HIDDEN TREATH. (29th May 2021) - Trevisani, Francesco; Di Marco, Federico; Rosiello, Giuseppe; Florio, Francesco; Cinque, Alessandra; Bettiga, Arianna; Capitanio, Umberto; Salonia, Andrea; Montorsi, Francesco
Abstract: Background and Aims: Acute kidney injury (AKI) is a major postoperative complication in renal surgery for cancer, both in radical than in partial nephrectomy. One of the most intriguing arguments is to understand if normal renal function patients without renal urinary abnormalities can develop post-operative AKI after renal surgery. Aim of our study was to compare the AKI incidence in the two major renal surgeries approaches (radical and partial nephrectomies) in a selected cohort of patients with normal renal function. Method: We performed a retrospective study of 216 patients who underwent radical (RN) or partial nephrectomy (PN) due to the presence of a kidney mass from 2000-2020 in a tertiary care Institution. Inclusion criteria: 1) Age> 18; 2) eGFR >;80 ml/min/1, 73 using CKD-EPI formula 2012 3) absence of urinary abnormalities 4) presence of two kidneys at time operation. The following data were considered: age, gender, body mass index (BMI), TNM staging, hypertension, diabetes. Serum creatinine values were collected before surgery (t 0), at 48 hours after surgery and at dismissal. GFR was estimated at each time point using creatinine-based estimated glomerular filtration rate (eGFR) formula: CKD-EPI. We evaluated eGFR variation from the pre-surgical value to 48 h post and at dismissal. eGFR categories were created according to the KDIGO guidelines for G categories. Comparisons between groups were performed using Kruskal-Wallis ranks sum test for numerical variables and Pearson's Chi square test for categorical variables. Logistic regression was used to identify variables ODDS Ratio for AKI onset after surgery. Results: Clinical and pathological characteristics are reported in table 1. The cohort was composed by 216 patients with median Age 55 (IQR: 47, 64), M/F ratio 2.4, median BMI 25.8 (IQR: 23.3, 28.4), median eGFR 94.3 (IQR: 89.1, 101.6). According to CKD G classes, 79% were stage 1 and 2 1 were stage 2. The cohort was divided in two groups according to the type of surgery: 51% as RN and 49% as PN. Differences between the two groups were detected for Gender (Radical M/F ratio: 3.3; Partial M/F ratio: 1.8; p=0.4), basal eGFR (Radical Median:92.9 (88.1, 101.0); Partial Median:95.3 (90.7, 102.4); p=0.03) and CKD G class (Radical I:64%, II:36%; Partial I:78%, II:22%; p=0.02). Logistic regression for AKI onset showed as significant parameter (p<0.001) only the type of surgery observing for Radical Nephrectomy and ODDS Ratio of 4.6 (Confidence Interval: 2.6, 8.5). The proportions of patients who developed AKI were 21% for PN and 55% for RN (Figure 1 ). Conclusion: Our study highlights that both radical (55%) than partial (21%) nephrectomies harbor a non-negligible risk of post-operative AKI even in normal renal function patients without renal abnormalities. In addition, the impact of RN in normal renal function patients shows a dramatic incidence of AKI in the 50% of cases, suggesting that nephron sparing surgeries techniques should be always indicated to preserve renal function also in patients with an eGFR> 80 ml/min/1, 73. A prospective comparison multicentric study with kidney living donor is on going.